The functional assessment as a key element in the recovery of football players after an injury - Gomez-Piqueras, P.; Gonzalez-Villora, S.; Sanchez-Gonzalez, M.; Sainz de Baranda, P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
Aim - The objective of this study was to establish reference values for professional football players in a series of previously selected functional tests. Methods - 42 professional football players were functionally assessed during two seasons (2012/13 and 2013/14), at three different times: preseason, midpoint of the season and end of the season. For this purpose, the following tests were carried out: Counter Movement Jump (bipodal jump), 5 metres Shuttle Run Sprint Test (speed/agility), Barrow Test (agility), Y Balance Test (posture control), Single Hop Test and Triple Hop Test (unipodal jump). Results - The average obtained values were: Counter Movement Jump (40.25±4.13cm), 5 metres Shuttle Run Sprint Test (10.89±0.38 seconds), Barrow Test (7.46±0.27 seconds), right asymmetry Y Balance Test (4.63±2.16%), left asymmetry Y Balance Test (3.91±2.25%), right Single Hop Test (2.06±0.11 meters), left Single Hop Test (2.07±0.12 meters), right Triple Hop Test (6.87±0.29 meters) and left Triple Hop Test (6.83±0.31). Conclusion - This paper contributes reference values which can be used to determine the sports performance or quantify the degree of functional recovery of an professional injured football player during his recovery.